Crushed ice ingestion does not improve female cycling time trial performance in the heat - Zimmermann, M.; Landers, G. J.; Wallman, K. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
This study examined the effects of precooling via ice ingestion on female cycling performance in hot, humid conditions. Ten female endurance athletes, mean age (28 ± 6 y), height (167.6 ± 6.5 cm) and body-mass (68.0 ± 11.5 kg) participated in the study. Participants completed an 800 kJ cycle time-trial in hot, humid conditions (34.9 ± 0.3 °C, 49.8 ± 3.5% RH). This was preceded by the consumption of 7 g·kg-1 of crushed ice (ICE) or water (CON). There was no difference in performance time (CON 3851 ± 449 s; ICE 3767 ± 465 s), oxygen consumption (CON 41.6 ± 7.0 ml·kg·min-1; ICE 42.4 ± 6.0 ml·kg·min-1) or respiratory exchange ratio (CON 0.88 ± 0.05; ICE 0.90 ± 0.06) between conditions (p > .05, d < 0.5). Core and skin temperature following the precooling period were lower in ICE (Tc 36.4 ± 0.4 °C; Tsk 31.6 ± 1.2 °C) compared with CON (Tc 37.1 ± 0.4 °C; Tsk 32.4 ± 0.7 °C) and remained lower until the 100 kJ mark of the cycle time-trial (p < .05, d > 1.0). Sweat onset occurred earlier in CON (228 ± 113 s) compared with ICE (411 ± 156 s) (p < .05, d = 1.63). Mean thermal sensation (CON 1.8 ± 2.0; ICE 1.2 ± 2.5, p < .05, d = 2.51), perceived exertion (CON 15.3 ± 2.9; ICE 14.9 ± 3.0, p < .05, d = 0.38) and perceived thirst (CON 5.6 ± 2.2; ICE 4.6 ± 2.4, p < .05, d = 0.98) were lower in ICE compared with CON. Crushed ice ingestion did not improve cycling performance in females, although perceptual responses were reduced.